How Abdominal Irrigation During Cesarean Delivery Affects Gastrointestinal Functions and Short-term Maternal Morbidities: A Randomized Controlled Study - Canan SATIR OZEL; Zelal Rojda GUNGORDU; Nisan Helin DONMEZ; Ergul DEMIRCIVI; Oguz Devrim YARDIMCI; Abdulkadir Turgut (Medeniyet Medical Journal)
Objective: This study aimed to investigate the effectiveness of intraabdominal irrigation with saline on postoperative gastrointestinal functions and short-term complications in patients who underwent cesarean section under general anesthesia. Methods: This prospective randomized controlled clinical trial was conducted between March 2022 and May 2022 and included 60 patients who underwent elective cesarean. The participants were randomized into two groups: abdominal irrigation (n=30) and control group (n=30). Participants undergo a standard cesarean procedure, and general anesthesia was preferred. The patients were questioned regarding nausea, vomiting, highest pain scores, time of flatus, and stool passage during the postoperative period. Results: Although no significant differences were found between the two groups (p>0.05), the return of bowel functions, i.e., passage of flatus and stool, occurred in a shorter period in the irrigation group (19.53 and 34.63 versus 16.73 and 33.7). The postoperative visual analog scale (VAS) scores of the two groups were comparable; VAS score of 4-6 was the sole difference when comparing both groups. Although postoperative vomiting was more common in the control group, no significant difference in postoperative vomiting, postoperative nausea, and postoperative antiemetic need was found between the two groups (p>0.05). Conclusions: The results revealed that intraoperative abdominal irrigation did not affect gastrointestinal functions and short-term maternal morbidity and did not provide additional benefits.